Delayed Anaphylactic Reaction to Midazolam in the Absence of Immediate Respiratory or Skin Manifestations - Andrew Winegarner; Mark C. Kendall; Mekhala Stephen; Afreen Siddiqui (Case Reports in Anesthesiology, 2023)
Anaphylaxis, a type 1 hypersensitivity reaction, is a feared but uncommon complication of medications administered in the perioperative period. The incidence of perioperative hypersensitivity reactions has been reported to range from 1 in 20,000 to 1 in 1,361. Anesthesiologists are well aware of common causes of hypersensitivity such as paralytics and antibiotics; however, less common triggers of anaphylaxis need to be considered as well. Midazolam, a short acting benzodiazepine metabolized by cytochrome P450 enzymes, is considered very safe with a minimal risk profile. Previous reports have described adverse reactions to occur within seconds to minutes following the administration of midazolam. We describe a patient with no known history of asthma or allergies who underwent elective hydrocelectomy with spinal analgesia without incident until 42 minutes later at the conclusion of the procedure, when they experienced circulatory collapse necessitating immediate emergency treatment. This case emphasizes the necessity to improve knowledge and awareness of delayed hypersensitivity reactions following the administration of perioperative medications such as midazolam.